SPESIASI DAN BIOAVAILABILITAS Pb DAN Cu DALAM TANAH PERTANIAN ORGANIK DI BEDUGUL SERTA KANDUNGAN LOGAM TOTALNYA DALAM SAYUR BROKOLI - Siaka, I M.; Nurcahyani, H.; Manuaba, I B. P. (Jurnal Kimia (Journal of Chemistry); Vol.13 No.2 Juli 2019, 2019)
Bedugul area is a vegetable producing center in Bali that also develops organic farming. This study aimed to determine the bioavailability of Pb and Cu in an organic farm in Bedugul and the content of both metals in broccoli before planting and at harvest. Metal extraction was carried out through wet digestion and its bioavailability was determined by the application of the sequential extraction methods. The measurement of the two metals was accomplished by using AAS. The total Pb content in the organic soils before and after harvesting were found to be 746.102-897.3754 mg/kg and 277.778-328.88217 mg/kg, while Cu were of  93.1212-11-114.3259 mg/kg, and 48,608-92.3708 mg/kg, respectively. The bioavailability of Pb and Cu in soils before planting was different from that of at harvest. Pb metal in organic soil before planting which were readily bioavailable, bioavailable, and nonbioavailable were were found to be (17.80-21.62)%, (44.07-47.65)%, and (30.73-36, 89 )%, while Cu were of (5.02-7.89)%, (55.73-60.57)%, and (32.81-39.25)%, respectively. The total Pb and Cu contents in broccoli were of (27,2968-30,3621) mg/kg and (27,0303-30,0223) mg/kg, respectively. Keywords : bioavailability, broccoli, organic agriculture soil, Pb and Cu, speciation